(untitled) - Associate Professor Dr. Nguyen Xuan Te (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The paper describes a general situation of dispute of the East Vietnam Sea and suggests an approach of solving the dispute from legal-political perspectives, that is solving the dispute of the East Vietnam Sea by peaceful solutions based on international laws.